2014
DOI: 10.1080/02614367.2014.962588
|View full text |Cite
|
Sign up to set email alerts
|

Music festival motivation in China: free the mind

Abstract: This paper explores the extent to which music festival attendance is 'universally' motivated or determined by the Chinese cultural and socio-political context.A novel qualitative approach was employed comprising observation of social media conversations and 'chat room' interviews with members of a festival online community. Seven motivators were identified, some similar to those in Western studies but others more specific to festival-goers in mainland China.The culturally specific motivators were identified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 66 publications
(112 reference statements)
5
53
0
1
Order By: Relevance
“…Lastly, a recent investigation of Chinese music festivals attendees found togetherness, musical enjoyment, and event novelty to be attendance motivators (Li & Wood, 2014). Overall, the motivational themes of music festival attendees gravitate towards socialization, musical enjoyment, and engagement with the festival atmosphere.…”
Section: The Previous Decades Have Witnessed the Creation Of Famous Mmentioning
confidence: 95%
“…Lastly, a recent investigation of Chinese music festivals attendees found togetherness, musical enjoyment, and event novelty to be attendance motivators (Li & Wood, 2014). Overall, the motivational themes of music festival attendees gravitate towards socialization, musical enjoyment, and engagement with the festival atmosphere.…”
Section: The Previous Decades Have Witnessed the Creation Of Famous Mmentioning
confidence: 95%
“…Although there is a small but growing body of literature on festival attendee's motivations in China (e.g., Y-N. Li & Wood, 2016), researchers are still unsure as to whether instruments designed by Western researchers are adaptable to China and the extent to which festival attendance is "universally" motivated (Dewar, Meyer, & Li, 2001). Research at a Chinese music festival by Y-N. Li and Wood (2016) found that although attendees have some similar motivations to those in Western studies, certain dimensions were more specific to festival goers in Mainland China. However, Dewar et al (2001) found that the motivational scales developed for festival attendees in North America were readily transferred to the Harbin Ice Lantern and Snow Festival in China.…”
Section: Wine Tourism and Wine Festivalsmentioning
confidence: 99%
“…The netnographic process outlined in this paper complements other recent leisure research (i.e. Jong & Murray, 2016;Li & Wood, 2016), and aims to apply a contemporary approach conscious of past criticisms of the methodology (Kozinets, 2016). This is ethnographic research conducted within and upon the new cultural coordinates mediated by contemporary networked communications, such as the internet, and the variety of devices that humans use to access it (Kozinets, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The approach has recently been extended to leisure studies (i.e. Jong & Drummond, 2016;Li & Wood, 2016), however remains underutilised and somewhat outside the mainstream (Mkono & Markwell, 2014). There is also growing critique of misuses of the method (Kozinets, 2015;.…”
Section: Introductionmentioning
confidence: 99%